GENERATION OF CR MAMMOGRAPHIC IMAGE FOR EVALUATION QUALITY PARAMETERS (Brazilian Journal of Radiation Sciences (BJRS), 2019)
Cancer is one of the leading causes of mortality in the world. In 2012, about 14 million new cases were registered, of which 1.6 million are breast cancer, according to the World Health Organization. The National Cancer Institute of Brazil estimated 57 thousand new cases of breast cancer by 2016. Mammography is the imaging technique most used worldwide for the early diagnosis of breast cancer. Computed radiography plates (CR) are used for digital radiography, and are widely used to obtain digital mammograms. The objective of this work is to evaluate the response of CR plates to the variation of exposure in mammographic equipment and to evaluate the viability of using calcium agglomerates as microcalcifications through the acquisition and evaluation of technical visual image quality, in order to develop a breast phantom of low cost and easy production using these structures. For the first goal, X-ray beams were selected to perform successive exposures of CR plates by varying the exposure time. These exposures were performed to obtain raw images that were subsequently analyzed using ImageJ software, from which the value of intensity recorded in the central region of each image was obtained, correlating it with the exposure time. From these data the necessary correlations were made to determine the exposure time for which the CR plate begins to saturate, observing that the saturation occurs first the CR plate of mammographic system A. For the second goal, successive exposures of the CR plate were made using the compressed breast simulator made of acrylic plates and containing microcalcifications of different sizes to determine the qualitative technical visual image quality of CR plates, observing that only microcalcifications above 177 μm are visible in the image.